Exome sequencing positively identified relevant alterations in more than half of cases with an indication of prenatal ultrasound anomalies. (3rd August 2015) - Alamillo, Christina L.; Powis, Zöe; Farwell, Kelly; Shahmirzadi, Layla; Weltmer, Elaine C.; Turocy, John; Lowe, Thomas; Kobelka, Christine; Chen, Emily; Basel, Donald; Ashkinadze, Elena; D'Augelli, Lisa; et al.
Abstract: Objective: Exome sequencing is a successful option for diagnosing individuals with previously uncharacterized genetic conditions, however little has been reported regarding its utility in a prenatal setting. The goal of this study is to describe the results from a cohort of fetuses for which exome sequencing was performed. Methods: We performed a retrospective analysis of the first seven cases referred to our laboratory for exome sequencing following fetal demise or termination of pregnancy. All seven pregnancies had multiple congenital anomalies identified by level II ultrasound. Exome sequencing was performed on trios using cultured amniocytes or products of conception from the affected fetuses. Results: Relevant alterations were identified in more than half of the cases (4/7). Three of the four were categorized as 'positive' results, and one of the four was categorized as a 'likely positive' result. The provided diagnoses included osteogenesis imperfecta II ( COL1A2), glycogen storage disease IV ( GBE1 ), oral–facial–digital syndrome 1 ( OFD1 ), and RAPSN ‐associated fetal akinesia deformation sequence. Conclusion: This data suggests that exome sequencing is likely to be a valuable diagnostic testing option for pregnancies with multiple congenital anomalies detected by prenatal ultrasound; however, additional studies with larger cohorts of affected pregnancies are necessary to confirm these findings. © 2015 John Wiley & Sons, Ltd. Abstract : What is already known about this topic? Diagnostic exome sequencing has been shown to be a successful option for diagnosing individuals, mostly pediatric patients, with previously uncharacterized genetic conditions. While some studies have included prenatal cases in their reported exome sequencing cohorts, little has been published specifically addressing the use of exome sequencing in a prenatal setting. What does this study add? This study reports the specific phenotype, family history, and alteration details from a small cohort of fetuses for which exome sequencing was performed. © 2015 John Wiley & Sons, Ltd.